Avaliação da capacidade de identificar emoções expressas pela face em adultos com lesão no hemisfério cerebral direito - Mucenecki, Thiago Ferreira (2016)
Several studies have focused on the contribution of the right hemisphere brain to the emotional aspects of communication, raising evidence that it is specialized in the emotional processing of faces. Right hemisphere brain damage (RHBD) may cause disturbances in the function mentioned, affecting social interactions since they depend on facial emotion recognition. This research aimed to contribute to the study of the possible impairment in the ability to identify facial expressions in 4 RHBD patients in order to elucidate whether those interfere with the performance of two emotion recognition instruments expressed by faces images. From a comparison between the RHBD group, 4 patients with left hemisphere brain damage (LHBD) and 8 subjects in the control group, we found 22 statistically significant or borderline statistical associations results (p≅0,05) only to the stimuli of the instrument Facial Expression Brazilian Task (FERBT), including the analysis of the emotional valences between LHBD and RHBD groups. Of these, 13 showed superiority of the control group in relation to clinical groups, and 9 showed superiority the LHBD group compared to the RHBD group. From this study, we can infer that FERBT is more congruent in relation to Emotion Recognition Index (ERI) concerning the hypothesis of brain asymmetry in facial expression recognition. The results of FERBT partially agrees with the hypothesis of emotional valence, since significant differences between clinical groups were found, favoring the LHBD group to the sum of emotion scores of negative valence at 500 milliseconds (ms), 1 second (s) and overall score of FERBT, adding up all the emotions in different times. However, it should be noted that borderline statistical associations differences favoring the LHBD group were found only for the emotion of fear (200ms and the total time) and anger (total time) with no significant differences for emotions of positive valence. This study helped to assess neuropsychological deficits after right hemisphere brain damage, since there is a significant gap in this diagnostic area. Through research, we can improve our knowledge about impairments caused by right hemisphere lesion by increasingly developing accurate assessment techniques and rehabilitation methods.